The International Research Collaboration, Learning and Promoting Innovation Capability in Indonesia Medical Sectors - Trina Fizzanty; Kusnandar Kusnandar; Sigit Setiawan; Radot Manalu; Dini Oktaviyanti (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2020)
Research collaboration accross countries is known as a promising strategy to enhance science and technology capacity and is more popular for researchers as it contributes to research productivity. In the context of a developing economy, like Indonesia, the goal of international research collaboration is to increase scientific capacity of researchers in developing economy, however limited information how the international research collaboration could promote innovation. This paper aims to reveal research results in medical research collaboration between institution in Indonesia and other countries and how the collaboration could promote innovation. Case study of eight international collaboration research projects in medical research were utilized, in which Indonesian researchers worked collaboratively with foresign researchers. The reseach found that international research collaboration has opened opportunities for Indonesian researchers to learn and upgrade their capability and be able to contribute to scientific knowledge. Collaborative research in the medical areana requires long term research and significant funding support. Based on the case studies, none of international research projects reached commercialization stage, because clinical research requires significant funding and the involvement of industry as clinical trials would enhance innovation. Keywords: international research collaboration, innovation capacity, medical innovation, collaboration process, Indonesia.